Bilateral spontaneous fracturing of the femoral neck in a patient with renal osteodystrophy()() - Garcia, Flavio Luís (Rev Bras Ortop, 2014)
We report a case of bilateral fracturing of the femoral neck in a patient with renal osteodystrophy who was treated by means of osteosynthesis. In this type of patient, there is a need to remain watchful for the possibility of occurrences of spontaneous fracturing of the femoral neck, even if the initial radiographic examination is normal.